Voter Turnout Among Compulsory Voting Countries: Evidence from 1973 to 2018 - Ikhsan Darmawan (Politicon : Jurnal Ilmu Politik, 2025)
Despite significant evidence that compulsory voting affects voter turnout, several compulsory voting countries had abandoned this law. It raises the query of whether compulsory voting affects voter turnout at the population level of compulsory voting countries. Additionally, how compulsory voting affects turnout also remains inconclusive, especially because most of the conclusions of previous studies were derived only from the case of parliamentary elections. Thus, this study’s objectives are twofold. First, this study seeks to explicate whether or not compulsory voting affects voter turnout in the compulsory voting countries. Second, this study also intends to explain whether the effect of compulsory voting on voter turnout vary across different types of elections. This study applies the theoretical explanation on the relationship between compulsory voting and voter turnout. This study employs quantitative methods, including linear regression models and Manova test results. By utilizing panel data of voter turnouts in 34 compulsory voting countries from 1973 to 2018, I found that the effects of compulsory voting on voter turnout appear in various conditions, either with or without sanctions and enforcement. In addition to that, I also found that the effects of compulsory voting vary across two types of elections, between compulsory voting and former compulsory voting countries. In particular, the effects of compulsory voting are higher in the presidential than in the parliamentary elections, except when compulsory voting is enforced. This paper could contribute to debates on abolishing compulsory voting in former compulsory voting countries or on adopting compulsory voting in countries interested in implementing this mechanism.